Study on high jumpers on the world - Gheorghe, D. (Science, Movement & Health, 2012)
This work has proposed that purpose, to separate the essential data for selection and training high performance athletes in the perspective of major international competition. Methods. As research methods I used the case study, observation and statistics. Results. For the final selection to the Olympics, to accede to one of the medals, the athlete`s performance should be over 2.30 m. If we have several athletes with special performances, we should focus primarily on those with a richer experience, with several international competitions, so a little older. Conclusions. In 2 of the 5 Olympics, the performance for the first place is equal to the average top, which confirms first hypothesis. The top average age is 24 years and 7 months which confirms the second hypothesis. The third hypothesis is confirmed with the observation that for the Olympics the performance is the supreme criterion, the height isn`t a decisive criterion (there are medalists with height below top average). The hypothesis of the athlete`s weight isn`t confirmed, recording an average of 77,36 kg. We only have significant correlation between athlete`s height and weight.